PEMBELAJARAN DALAM MASA PANDEMI COVID-19 - Rendy Rinaldy Saputra (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2021)
ABSTRACT The background of conducting the research is to explore the problems faced in implementing learning activities during the Covid-19 pandemic with the aim of knowing 1) how to implement learning during the Covid-19 pandemic, and 2) what are the obstacles in implementing learning during the Covid-19 pandemic. The research was conducted with a qualitative approach by conducting a study of previous research. The data analyzed in the study were obtained through Google Scholar pages with the keyword "covid-19 and education". A search on the google cendikia page refers to 6 journals that meet the research criteria. Based on the results of the research data analysis, it can be concluded that several things include: 1) online learning is the best effort that can be done in order to break the chain of the spread of the covid-19 virus, especially in the field of education, 2) Online learning can be done using various internet-based applications such as WhatsApp Group, Zoom Cloud Meeting, Google Classroom, Google Form, Quipper, e-mail and ect, 3) the obstacles faced in implementing online learning activities include the lack of supporting facilities and infrastructure, unstable internet services, requiring a large enough quota, not yet evenly distributed human resources who master technology well, communication in the learning process does not go well, limited learning methods are applied in learning activities, and lack of supervision of the development of students. Keywords: covid-19 pandemic, learning, online